Policy Analysis of Bank Indonesia Concerning Finance to Value (FTV) to Minimize Problem Financing of Sharia Home Ownership Loans (KPR - Paramita, Nadira; Suggianto, Sugianto; Jannah, Nurul (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The Financing to Value (FTV) policy is a macroprudential policy issued by Bank Indonesia to determine the total ratio between the value of credit that can be provided by a bank to the value of collateral in the form of property at the time of initial lending to customers. This research aims to be able to know how the procedures for implementing risk management in Sharia Home Ownership Loans (KPR) financing and knowing FTV policies can minimize problem financing on Sharia KPR products at Bank Muamalat Branch Office (KC) Medan City Hall. In this study, the authors used qualitative research with a case study approach. Data collection techniques used interviews and documentation. From the results of the research conducted, it was found that Bank Muamalat KC Medan City Hall has fully implemented Bank Indonesia’s policy regarding Finance to Value (FTV) in KPR financing products. However, this implementation is not fully in accordance with existing policies and the application of these policies has not fully minimized the NPF of Sharia KPR. In addition, the implementation of Sharia Home Ownership Loans (KPRS) distribution carried out by Bank Muamalat KC Medan City Hall did not go well due to several things that caused problematic financing, including non-performing loans. Problematic credit financing at Bank Muamalat KC Medan City Hall is caused by two things, namely debtors and creditors. To prevent and overcome problem financing loans that have been carried out by Bank Muamalat KC Medan City Hall, namely by providing understanding to debtors and providing concessions to ongoing credit problems.